Development of the Russian socio-economic system: challenges and prospects - Kiselev A. A., Soldatova L. I., Shmidt I. I., Fadeeva G. V., Boboshko A. A., Kharlanov A. S., Lapshin V. I., Beketova O. N., Sedov I. D., Bagirova A. R., Loseva E. S., Fedorova I. A., Dashian S. G., Fedulova E. A., Burtseva E. V., Medvedeva S. V., Ivaniuzhenko A. B., Shchankina L. N., Voronenko E. A., Piatitskaia D. V., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Lavina T. A., Gritsevich T. I., Russova N. V., Zakharova A. N., Paevskaia S. L., Mironova N. G. (Development of the Russian socio-economic system: challenges and prospects, 2024)
the main source of income for any person is wages. It also helps to control the measure of labor and consumption. Therefore, wages can be considered as an economic lever for managing the economy of an enterprise. Wages act as a central factor that has a direct impact on the productivity of employees. This is the incentive for which a person works in a company. Today, the state pays special attention to the development of multiple regulations that regulate the payment of salaries to employees. First of all, it is necessary to build a wage system in the company as competently as possible. The system should be as clear as possible for each employee, because it is through it that he sees the relationship between productivity, as well as the quality of work and the amount of wages. Depending on what the wages will be, the standard of living of citizens depends, and this is an extremely important factor in the development of the state as a whole. When wages are reduced, expenses in all areas are reduced, and this also leads to an increase in unemployment.
Keywords: анализ; эффективность; труд; оплата труда; efficiency; analysis; заработная плата; задолженность; labor; фонд оплаты труда; debt; коэффициенты; remuneration; wages; показатели изменения выработки; coefficients; indicators of change in output; wage fund